2021
DOI: 10.2196/25820
|View full text |Cite
|
Sign up to set email alerts
|

A Personalized Mobile Health Program for Type 2 Diabetes During the COVID-19 Pandemic: Single-Group Pre–Post Study

Abstract: Background With increasing type 2 diabetes prevalence, there is a need for effective programs that support diabetes management and improve type 2 diabetes outcomes. Mobile health (mHealth) interventions have shown promising results. With advances in wearable sensors and improved integration, mHealth programs could become more accessible and personalized. Objective The study aimed to evaluate the feasibility, acceptability, and effectiveness of a persona… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 62 publications
2
43
0
Order By: Relevance
“…Heterogeneity in the study types was observed as follows: cross-sectional (n = 9; 53%), longitudinal (n = 4; 24%), retrospective (n = 1; 6%), narrative review (n = 1; 6%) and pilot non-randomized studies (n = 2; 12%). Similar heterogeneity was found in participants too in the included studies: pregnant women [27], elderly [24,26], office workers [21], diabetes [18] and children [25]. All the studies were from high-income countries.…”
Section: Resultssupporting
confidence: 60%
See 4 more Smart Citations
“…Heterogeneity in the study types was observed as follows: cross-sectional (n = 9; 53%), longitudinal (n = 4; 24%), retrospective (n = 1; 6%), narrative review (n = 1; 6%) and pilot non-randomized studies (n = 2; 12%). Similar heterogeneity was found in participants too in the included studies: pregnant women [27], elderly [24,26], office workers [21], diabetes [18] and children [25]. All the studies were from high-income countries.…”
Section: Resultssupporting
confidence: 60%
“…From the evidence included, we found a significant increase in the use of wearables to improve physical activity during the confinement or lockdown periods [21,24]. There is a convincing evidence to show that there is a significant decrease in physical activity and increased sedentary time in people around the world when judged objectively using wearables [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Figure 2 represents the summary of our findings.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations